Unraveling the association between major depressive disorder and senescent biomarkers in immune cells of older adults: a single-cell phenotypic analysis - Lorenzo, Erica C.; Figueroa, Jovany E.; Demirci, Derya A.; El-Tayyeb, Ferris; Huggins, Billy J.; Illindala, Medha; Bartley, Jenna M.; Haynes, Laura; Diniz, Breno S. (Frontiers in Aging, 2024)
Background: Little is known about the prevalence of cellular senescence among immune cells (i.e., immune cells expressing senescence markers, iSCs) nor is there a gold-standard to efficiently measure iSCs. Major depressive disorder (MDD) in older adults has been associated with many hallmarks of senescence in whole blood, leukocytes, and plasma, supporting a strong connection between iSCs and MDD. Here, we investigated the prevalence and phenotype of iSCs in older adults with MDD. Using a single-cell phenotypic approach, circulating immune cells were examined for iSC biomarkers and their relationship to depression and inflammation. Results: PBMCs from older adults with MDD (aged 69.75 ± 5.23 years) and healthy controls (aged 71.25 ± 8.8 years) were examined for immune subset distribution and senescence biomarkers (i.e., lack of proliferation, senescence-associated heterochromatin foci (SAHF), and DNA damage). Dual-expression of SAHF and DNA damage was categorized by low, intermediate, and high expression. A significant increase in the number of high expressing total PBMCs (p = 0.01), monocytes (p = 0.008), a trending increase in the number of high expressing CD4 T cells (p = 0.06) was observed overall in those with MDD. There was also a significantly lower proportion of intermediate expressing cells in monocytes and CD4 T cells in MDD (p = 0.01 and p = 0.05, respectively). Correlation analysis revealed associations between iSCs and mRNA expression of factors related to SASP and immune cell function. Conclusion: MDD is associated with increased senescent cell biomarkers in immune cell populations delineated by distinct levels of SAHF and DNA damage. Inflammatory markers might serve as potent indicators of iSC burden in MDD.